Non‐Hookean Droplet Spring for Enhancing Hydropower Harvest. Issue 18 (6th April 2022) - Xue, Luanluan; Li, Huizeng; Li, An; Zhao, Zhipeng; Li, Kaixuan; Li, Mingzhu; Song, Yanlin
Abstract: Nonlinear elastic materials are significant for engineering and micromechanics. Droplets with the merits of easy‐accessibility, diversity, and energy‐absorption capability exhibit a variety of non‐Hookean elastic behaviors. Herein, benefiting from the confinement of heterogeneous‐wettable parallel plates, the non‐Hookean mechanics of the droplet‐based spring are systematically investigated. Experimental results and theoretical analysis reveal that the force generated by the spring varies nonlinearly with its deformation, and a force model is accordingly built to depict the mechanics of springs with different sized/numbered droplets and confined by different wettability patterns. Importantly, for the droplet‐based spring, the droplet‐plate contact area expands nonlinearly with the pressing force, which is employed to optimize the output performance of the droplet‐based triboelectric nanogenerator to 226% compared with the control test. This finding deepens the understanding of the non‐Hookean behavior of droplet‐based springs, and sheds light on applications in energy harvesting, micromechanics, and miniature optic/electric devices. Abstract : A non‐Hookean droplet‐based spring is fabricated with heterogeneous‐wettable parallel plates and confined droplets. The compressive/tensile force varies nonlinearly with the deformation, and the mechanics can be precisely tuned by the properties of droplets and wettability patterns. Moreover, the droplet‐plate contact area varies nonlinearly with the pressing force, which is utilized to enhance hydropower harvest efficiency to 226% compared with the control test.